2017
DOI: 10.1177/0898264317726390
|View full text |Cite
|
Sign up to set email alerts
|

Education Inequalities in Health Among Older European Men and Women: The Role of Active Aging

Abstract: Policies devoted at stimulating an active participation in society among older people should be particularly focused on lower educated groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
1
16
0
4
Order By: Relevance
“…Our dependent variable is the number of depressive symptoms, measured using the EURO-D scale, which is composed of 12 items, each measuring the presence of a specific depressive symptom. We used this variable as cardinal, ranging from 0 to 12, as done by e.g., Arpino and Solé-Auró (2019). We also carried out the analyses by dichotomizing the EURO-D scale in a way that considered the presence of depression with scores higher than 4 (Crimmins et al 2011;Prince et al 1999) and results (available on request) were qualitatively similar to those presented here.…”
Section: Datamentioning
confidence: 86%
“…Our dependent variable is the number of depressive symptoms, measured using the EURO-D scale, which is composed of 12 items, each measuring the presence of a specific depressive symptom. We used this variable as cardinal, ranging from 0 to 12, as done by e.g., Arpino and Solé-Auró (2019). We also carried out the analyses by dichotomizing the EURO-D scale in a way that considered the presence of depression with scores higher than 4 (Crimmins et al 2011;Prince et al 1999) and results (available on request) were qualitatively similar to those presented here.…”
Section: Datamentioning
confidence: 86%
“…Other studies found that older adults with a lower education level were less likely to participate in social activities (49,50). Policies that aims to promote the productive participation of older adults in social activities should focus on groups with lower education levels (51).…”
Section: Discussionmentioning
confidence: 97%
“…Our study makes a relevant contribution to the existing literature in the field given that, although some determinants of the emotional well-being of the elderly are known [8,10,18], to the best of our knowledge there are no studies that consider the magnitude of the association between the main variables linked to positive mental well-being and the rural or urban characteristics of the living environment.…”
Section: Purpose and Contribution Of The Studymentioning
confidence: 96%
“…Levels of education and income may also influence mental well-being. Some results for Europe show that educational inequalities in health can be partially explained by different levels of active ageing engagement [18], as older people with high levels of education reported higher engagement in active ageing activities. Evidence from the US [19] found that income and education are closely related to evaluation of life, while health, care giving, loneliness and smoking are more closely related to daily emotions.…”
Section: Mental Well-being Among Older Individualsmentioning
confidence: 99%